Propuesta para la mejora en la reposición de inventario en una empresa retail peruana mediante herramientas lean - Lino Robles, Renato André (2024)
This research work aims to improve inventory replenishment in a retail company as it is essential for any company to meet product demand. Therefore, by analyzing the percentage of canceled orders within the retail company and using an Ishikawa diagram, it was determined that the absence of distribution centers led to cost overruns in the logistics process. By employing this methodology, the improvement proposal was divided into three stages: logistics hubs information collection and diagnosis; design and validation of the improvement proposal; and evaluation of the improvement proposal viability, risks and implementation time. These stages indicate that the proposed solution would involve establishing a logistics hub to serve as a low-cost distribution warehouse. Furthermore, during this research, we used the 5S methodology, one of the most popular lean tools, applicable to every department and action. Based on the analysis of the cost flow and economic scenarios, it is concluded that implementing the hub is feasible. This would not only increase product availability and assortment but also result in savings on transportation costs from the distribution center in Lima to the hub located in Tarapoto, Peru.